The therapeutic benefits of natural cannabinoids in delaying the pathophysiology of Alzheimer's disease (Research, Society and Development, 2021)
Objectives: To analyze and evaluate the current conjuncture inherent to the therapeutic use of natural cannabinoids in delay and protection against the pathophysiological actions caused by Alzheimer's disease. Methods: Overview of systematic reviews. The search and selection of the studies were predominantly in the databases of the Medical Literature Analysis and Retrieval System Online (Medline), National Library of Medicine (Pubmed) and Scientific Electronic Library Online (SciELO) in  the period between March and August  2020.  Key ﬁndings: Current results showed promising therapeutic effects of natural cannabinoids in the treatment of Alzheimer's disease, such as reduction of motor and cognitive symptoms, and protective neuroprotective action. These results can be explained, in part, by the anti-inflammatory, antioxidant, antagonist action of CB1 receptors, as well as by the activation of PPAR-gamma receptors produced by these substances. Conclusions: The systematic research presented in this overview converges in the sense that the therapeutic applications provided by natural cannabinoids and their analogues may play a unique role in the modulation of molecular targets involved in central nervous system dysfunctions caused by Alzheimer's disease, thus enabling the development of innovative drugs, safer and more effective in the treatment of patients not responsive to conventional clinical practice, with significant improvement in quality of life.